As políticas sociais no Brasil: um estudo de caso no Rio Grande do Sul sobre o Programa Bolsa Família durante o governo Lula - Alves, Marco Antonio Sampaio (2016)
The main objective of the following study is to analyze the impact of social policies adopted by the government of Brazil's former President, Luiz Inácio Lula da Silva, focusig on the Bolsa Família Program in Rio Grande do Sul. As such, this study aims to explore, from a historical perspective, the trajectory of social policies in the country. Subsequently, an analysis of the Lula Adminstration will be made and we'll hold a discussion regarding social policy as part of “neo-developmentalism” policies, which ended up on the agenda of said government – taking central stage in the recovery of the role of the State – so that Brazil could then resume the fight to overcome underdevelopment. This way, the Bolsa Família Program has been articulating itself into an expectation to revert two of the country's historical problems: poverty and inequality. Therefore, recovering the characteristics of social policy in Brazil, this research proposes to assess the impact of the Bolsa Família Program in the reduction of poverty and inequality in the State of Rio Grande do Sul from 2004 to 2010, a period which comprises the Lula Administration.